Pengarusutamaan Hukum Perubahan Iklim dalam Kurikulum Pendidikan Tinggi Hukum di Indonesia: Mainstreaming Climate Change Law into the Legal Higher Education Curriculum in Indonesia - Dwi Rafiqi, Ilham; Fartikasari, Elsa Diana (Perspektif Hukum, 2026)
Climate change is a global challenge with cross-sectoral impacts, including in the legal realm. Although climate change legal regulations have developed at both the international and national levels, their integration into the Indonesian legal education curriculum remains limited. This study aims to analyze the urgency and momentum of recognizing climate change law in the legal education curriculum, and to identify strategies for integrating climate law substance into legal learning. The method used is normative research with a conceptual approach and a comparison of the curricula of several law schools in Indonesia. The results indicate a gap between the complexity of climate change legal issues and the readiness of legal education institutions to equip students as future legal practitioners who are responsive to global environmental issues. The momentum of increasingly progressive national and international regulations on climate change issues should be utilized by legal education institutions to reform their curricula to be more contextual and interdisciplinary. This study recommends the need to integrate climate change law as a stand-alone course or as part of an environmental law course, as well as strengthening transdisciplinary approaches in legal education to produce adaptive and sustainable graduates.